2000
DOI: 10.1105/tpc.12.6.963
|View full text |Cite
|
Sign up to set email alerts
|

cDNA-AFLP Reveals a Striking Overlap in Race-Specific Resistance and Wound Response Gene Expression Profiles

Abstract: The tomato Cf-9 gene confers resistance to races of the fungal pathogen Cladosporium fulvum expressing the Avr9 gene. cDNA amplified fragment length polymorphism analysis was used to display transcripts whose expression is rapidly altered during the Avr9-and Cf-9 -mediated defense response in tobacco cell cultures. Diphenyleneiodonium was used to abolish the production of active oxygen species during gene induction. Of 30,000 fragments inspected, 290 showed altered abundance, of which 263 were induced independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
182
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(201 citation statements)
references
References 65 publications
12
182
1
1
Order By: Relevance
“…The plant is clearly sensing the presence of the nematode within the Wrst 6 h of infection as shown by a rapid increase in gene expression. Rapid stimulation of genes involved in defense is not uncommon in soybean (Droge-Laser et al 1997;Park et al 2004b) and these processes can account for as much as 1% of new transcripts within the Wrst 15 min of infection (Durrant et al 2000). Transcript proWles with similar topology to our proWles 1, 3, and 4 were observed in Arabidopsis roots infected with the gall forming nematode Meloidogyne spp.…”
Section: Timecourse Microarray Analyses Of H Glycines Infection Of Gsupporting
confidence: 61%
“…The plant is clearly sensing the presence of the nematode within the Wrst 6 h of infection as shown by a rapid increase in gene expression. Rapid stimulation of genes involved in defense is not uncommon in soybean (Droge-Laser et al 1997;Park et al 2004b) and these processes can account for as much as 1% of new transcripts within the Wrst 15 min of infection (Durrant et al 2000). Transcript proWles with similar topology to our proWles 1, 3, and 4 were observed in Arabidopsis roots infected with the gall forming nematode Meloidogyne spp.…”
Section: Timecourse Microarray Analyses Of H Glycines Infection Of Gsupporting
confidence: 61%
“…To confirm complete transfer of RNA to the membrane filter, both gel and membrane were viewed under UV light after transfer. The filter was hybridized to a 32 P-labeled pCa-DSR probe as indicated The polypeptides encoded by Ca-DSR2 and Ca-DSR7 show similarity to the ERF/AP2-domain-containing transcription factors identified in tobacco (Durrant et al 2000) and Arabidopsis (GenBank Accession No. NP_200015), respectively (Table 1).…”
Section: Isolation and Identification Of Drought Stress-related Genesmentioning
confidence: 99%
“…The predicted molecular mass of the polypeptide encoded by pCa-DREBLP1 is 23.8 kDa with a calculated pI of 6.34. Database searches revealed that Ca-DREBLP1 is most closely related to the tobacco NtAvr9/Cf-9 elicited protein (Durrant et al 2000) and tomato LeCBF1 (Jaglo et al 2001), with 69% and 61% identity at the amino acid level, respectively (Fig. 2b).…”
Section: Isolation and Identification Of Drought Stress-related Genesmentioning
confidence: 99%
“…ATL54 has been reported to function in secondary cell wall formation (Noda et al 2013), and ATL14, also designated IDF1, has been found to regulate Fe uptake via the ubiquitination of the Fe transporter IRON-REGULATED TRANSPORTER1 (IRT1) (Shin et al 2013). In addition to Arabidopsis, ATL isoforms are involved in defense responses in varied plant species; e.g., EL5 and BIRF1 in rice (Liu et al 2008;Takai et al 2002), StRFP1 in potato (Ni et al 2010) and ACRE132 in tobacco (Durrant et al 2000). EL5 is also involved in root meristem development via cytokinin-mediated nitrogen effect in rice (Koiwai et al 2007;Mochizuki et al 2014).…”
Section: Plant Specific Ubiquitin Ligase Atl Familymentioning
confidence: 99%